Chemical weapons, Ayatollah Khomeini and Islamic law. Issue 1 (1st January 2017) - Simonen, Katariina
Abstract: The purpose of this article is to revive academic discussion about the potential of Islamic norms to affect State policy with regard to weapons of mass destruction. A number of religious norms govern just warfare ( jus in bello ). Yet, the extension of such norms to weapons of mass destruction, let alone their effect on State policy, has been under-researched not only by Western scholars but also by Islamist ethicists. This case study sets out to discuss different contextual aspects of the role played by religion in Iranian decision-making in relation to chemical weapons during the Iran–Iraq War (1980–1988). Iran constitutes a sui generis case when it comes to evaluating the power of religious norms to affect policy. This is due to religion's major role in the society's cultural and constitutional structure. Iraq started using chemical weapons ('CW') against Iran in 1982 and continued to do so through the war. Iran did not respond in kind, initially. Religious norms played a role in Iran's restraint, but their compliance pull was not absolute. A number of internal factors resulted in the religious prohibitions as well as a number of grand jurists ( marāji' - i taqlīd ) being sidelined, which paved the way for some CW use and development by Iran. External factors also played a part when the restraint exercised by religious norms was weakened. During the war, the international community remained mostly passive. This type of prioritising of other considerations over concerns of humanity sent a clear message to the Iranian decision-makers. The religious/moral argument was set aside. There are clear lessons for non-proliferation policy to be learned from the Iranian case. The religious argument can play a role in restraining State policy. However, it does not operate in a vacuum. It also needs the unconditional support of external actors engaged in non-proliferation.